The Role of International Arbitration in Resolving Cross-Border Commercial Disputes - Sulton, Ahmad; Fikri, Abdillah (Justicia Insight, 2025)
International arbitration has emerged as a preferred mechanism for resolving cross-border commercial disputes due to its neutrality, flexibility, and enforceability. This study examines the pivotal role of international arbitration in addressing conflicts arising from global trade and investment activities. It explores the advantages of arbitration over traditional litigation, including party autonomy, procedural efficiency, confidentiality, and the recognition of arbitral awards under the New York Convention. Furthermore, the research highlights the challenges faced in arbitration practice, such as high costs, lengthy proceedings, and the need for harmonization across different legal systems. By analyzing key cases and international instruments, this paper underscores the significance of arbitration in promoting legal certainty, protecting business interests, and fostering international economic relations. The findings suggest that while arbitration remains an indispensable tool in global commerce, reforms are necessary to enhance its accessibility and effectiveness in resolving complex cross-border disputes.